2018
DOI: 10.1007/s13193-018-0812-0
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Experience of Renal Cell Carcinoma from a Tertiary Care Teaching Institute in North India

Abstract: To study the current trends of renal cell carcinoma (RCC) in terms of demographic characteristics, clinical presentation, staging, mode of management, histopathology, and survival characteristics from a high volume tertiary care teaching institute in North India. We retrospectively reviewed the records of all patients of RCC between January 2006 and December 2015 and variables like age, gender, symptoms, tumor size/location/number, stage, type of surgery, histopathology, and survival characteristics were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our study reports that the disease is more common among males (58.5%) and in the fifth decade of life (mean=52.6 years). This was comparable to a study by Kawaljit et al in 2018, who reported the disease as most common in the 50-59 age group, followed by 60-69 years. In their study, predominantly affected patients were males, with a much greater percentage of 71.5%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study reports that the disease is more common among males (58.5%) and in the fifth decade of life (mean=52.6 years). This was comparable to a study by Kawaljit et al in 2018, who reported the disease as most common in the 50-59 age group, followed by 60-69 years. In their study, predominantly affected patients were males, with a much greater percentage of 71.5%.…”
Section: Discussionsupporting
confidence: 89%
“…However, it is still regarded as the deadliest urological cancer worldwide. 9 Survival rate largely depends on the stage of the tumour at the time of diagnosis. Early diagnosis followed by early treatment results in a better prognosis, but as the Fuhrman Grades progress to III and IV, the survivability of the patient reduces considerably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A study done in India has shown that most prevalent stage in .the patients of RCC presenting to them was stage 2 seen in 45.5% patients. 25 Different stages prevalence is seen in literature showing variations among developed and under developed countries indicating the health awareness, basic health facilities and socioeconomic status in the country.…”
Section: Discussionmentioning
confidence: 99%